2017
DOI: 10.1002/hyp.11163
|View full text |Cite
|
Sign up to set email alerts
|

Cokriging for enhanced spatial interpolation of rainfall in two Australian catchments

Abstract: Rainfall data in continuous space provide an essential input for most hydrological and water resources planning studies. Spatial distribution of rainfall is usually estimated using ground-based point rainfall data from sparsely positioned rain-gauge stations in a rain-gauge network. Kriging has become a widely used interpolation method to estimate the spatial distribution of climate variables including rainfall. The objective of this study is to evaluate three geostatistical (ordinary that among the geostatist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 48 publications
2
52
0
2
Order By: Relevance
“…Based on visual inspection and quantitative appraisal both for interpolated values and standard errors, it is suggested that CK (with soil cohesion as covariate) performs better than IDW and OK in estimating spatial distribution of soil depth to hardpan in Western Central Java. This is consistent with the aim of Cokriging model development (Myers 1984) and its implementation 5 (Minnitt and Deutsch 2014;Adhikary et al 2017;Xie et al 2018).…”
Section: Interpolation Performancesupporting
confidence: 81%
“…Based on visual inspection and quantitative appraisal both for interpolated values and standard errors, it is suggested that CK (with soil cohesion as covariate) performs better than IDW and OK in estimating spatial distribution of soil depth to hardpan in Western Central Java. This is consistent with the aim of Cokriging model development (Myers 1984) and its implementation 5 (Minnitt and Deutsch 2014;Adhikary et al 2017;Xie et al 2018).…”
Section: Interpolation Performancesupporting
confidence: 81%
“…Considering the topography and sparse rain gauge stations, we adopted a geostatistical approach, co-kriging for estimation of areal average gauge-based precipitation. A detailed description and procedure of co-kriging are presented in [29,30]. Several statistical indices (continuous evaluation indices and categorical indices) were adhered for investigation of accuracy (of TMPA precipitation products) in terms of consistency and discrepancy [25,31].…”
Section: Methods For Accuracy Assessmentmentioning
confidence: 99%
“…On the other hand, the performance of the CK method could be ascribed to the very frequent application of an elevation correction factor in the case of the CK-based dataset. The CK method was found to be useful for regionalization of hydrological signatures [5,51]. It solved a problem of hydrological modeling in that the precipitation data were poorly resolved in space and could not capture heterogeneous orographic effects [52].…”
Section: Analysis Of Runoff Process By Spatial Interpolation Of Precimentioning
confidence: 99%